The influence of attentional focus on the learning of long-distance throwing - Oki, Y.; Kokubu, M. (Japanese Journal of Sport Psychology, 2021)
The present study examined the influence of attentional focus on learning long-distance throwing. Twenty-one participants (14 male and 7 female, mean age: 21.9±1.8 years) completed the pre-test, 10 learning sessions (each 15 trials), and post-test. In the learning sessions, they were assigned to one of three groups of attentional focus: the wrist internal, torso internal, and external focus groups. On the pre-test and post-test, they executed three trials under all three conditions of attentional focus. Results showed that the effect of learning sessions on throwing distance differed by attentional focus. For the two internal focus groups, the throwing distances were longer in the last session than the first, while the external focus group did not show an effect of learning sessions. On the pre-test and post-test, the external focus condition showed the longest throwing distance of all attentional focus conditions. In addition, there was a positive correlation between the rates of increase in throwing distance and release angle, but no correlation between the rates of increase in throwing distance and initial velocity. These results suggest that internal focus is more effective than external focus in learning long-distance throwing, whereas external focus is more effective for long-distance throwing performance.